(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
This article analyzes the ergonomic application of composition principles in engineering graphics and clothing design. The scientific and practical aspects of compositional structure are covered based on ergonomic factors such as human body proportions, movement dynamics, and adaptation to the environment. It also examines the methodology for applying the principles of composition, harmony, proportion, rhythm, and contrast in engineering drawing, construction graphics, and fashion design on an ergonomic basis.